Praktikum za ustavno pravo - Dacar, Rok (2025)
Constitutional Law Casebook. The Constitutional Law Casebook is designed for in-depth study of fundamental constitutional law concepts and institutions through the analysis of selected decisions of the Constitutional Court of the Republic of Slovenia. It serves as a didactic tool for law students who face the challenges of understanding and applying constitutional law in practice. Special emphasis is placed on recent case law, which significantly contributes to the development and interpretation of the constitutional order. The practicum encourages critical thinking, argumentation, and discussion, enabling students to gain insight into the functioning of constitutional review and the importance of protecting constitutional rights in contemporary society.
Keywords: Constitutional Court; case law; fundamental rights; state organization; constitutional complaint